A detailed Auger electron spectroscopy study of the first stages of the growth of C60 thin films - Vidal, Ricardo Alberto (2015)
In this work we take advantage of the large sensitivity and in-depth resolution of Auger electron spectroscopy to study in a detailed way the growth of C60 over different substrates, namely Cu(111), Si(100) and graphene. The ability of AES, as compared to more local probes like STM or AFM, to follow the process in a dynamical way, allows us to study the growth of C60 below and over one ML, including the change of C60 over either Si or Cu to the growth of C60 over a C60 film. We found that the growth proceeds always as layer by layer. This result shows that differences in diffusion barriers are not as important as one can think following the idea of diffusion by a jumping mechanism. We propose that the sticking coefficient, governed by the adsorption energy, is the responsible of the differences observed between Cu and Si. Our results also point out to a different charge transfer among fullerene molecules and these surfaces. The same result is suggested in the case of C60 over graphene, but in this case our conclusion comes from the variable temperature experiments.